Modeling the influence of biomass burning haze on extreme rainfall events - Oyegbile, Ollamilekan Oluwatobi (2025)
Biomass burning is a major contributor to atmospheric aerosols globally, releasing over 2 Pg C annually, with West Africa experiencing widespread biomass burning during the December-February dry season that results in a thick haze layer known as the "Harmattan." This seasonal phenomenon significantly impacts air quality and regional climate across the region, with major cities like Lagos, Nigeria (population exceeding 14 million) being particularly vulnerable to compounding impacts of seasonal biomass burning pollution. Devastating flood events, such as those occurring on July 10, 2011, and July 16, 2021, have resulted in significant infrastructural damage and loss of human life in Lagos. While growing evidence suggests that the Saharan Air Layer and Harmattan haze may play a crucial role in modulating West African monsoon patterns and rainfall intensity, there remains a critical knowledge gap regarding the specific impacts of biomass burning emissions on extreme precipitation events and urban flooding in rapidly developing coastal megacities. Despite emerging insights into aerosol-climate interactions, limited research has quantified the direct influence of long-range transported biomass-burning aerosols within the Harmattan haze layer on anomalous precipitation and flooding in coastal population centers.